For a quadratic function define
Among every satisfying the below condition, the minimum of is which occurs at
Find the value of
1. For all and
2. For all we have
3. Function is differentiable over all reals.
This problem is a part of <Christmas Streak 2017> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since g ( x ) = x + ln f ( x ) , we have g ′ ( x ) = 1 + f ( x ) f ′ ( x ) .
Now let f ( x ) = a x 2 + b x + 1 , then because of [1.] we have b 2 < 4 a and a > 0 .
From [2.] we see that 1 + f ( x ) f ′ ( x ) ≥ 0 , which leads us to f ( x ) + f ′ ( x ) ≥ 0 .
a x 2 + ( 2 a + b ) x + b + 1 ≥ 0 ⇔ D = 4 a 2 + b 2 − 4 a ≤ 0 .
In [3.] , ∣ g ( x ) − g ′ ( 0 ) x ∣ = ∣ ∣ ∣ ∣ x + ln f ( x ) − x − f ( 0 ) f ′ ( 0 ) x ∣ ∣ ∣ ∣ = ∣ ∣ ln ( a x 2 + b x + 1 ) − b x ∣ ∣
Letting x = 0 , we note that two graphs y = ln ( a x 2 + b x + 1 ) and y = b x intersects at the origin.
Then let h ( x ) = ln ( a x 2 + b x + 1 ) .
h ′ ′ ( x ) = ( a x 2 + b x + 1 ) 2 − 2 a 2 x − 2 a b x − b 2 + 2 a , and D / 4 = ( a b ) 2 − 2 a 2 ⋅ ( b 2 − 2 a ) = a 2 ( − b 2 + 4 a ) > 0 .
Therefore y = h ( x ) has two inflection points.
h ( x ) is a logarithmic function, which means as x tends to either infinity, the graph is concave.
This tells us that the abstract shape of h ( x ) would be [ − ∞ ← concave ] − [ convex ] − [ concave → ∞ ] .
So for ∣ h ( x ) − b x ∣ to be differentiable over all reals, we need to have y = b x tangent to y = h ( x ) at the local minimum, or at the inflection point.
i ) tangent at the local minimum
Then b = 0 , leading to f ( x ) = a x 2 + 1 ≥ 1 , telling us that f ( x ) ≥ 1 .
i i ) tangent at the inflection point
Then y = b x is the inflection tangent line of y = h ( x ) at the origin, and from h ′ ( 0 ) = b (which is pretty useless) and h ′ ′ ( 0 ) = 0 , we get that b 2 = 2 a .
From before we found that 4 a 2 + b 2 − 4 a ≤ 0 . Plug that in, and we get 2 a 2 − a ≤ 0 ⇔ 0 < a ≤ 2 1 and 0 < b 2 ≤ 1 .
Since f ( k ) = a k 2 + b k + 1 = 2 1 b 2 k 2 + b k + 1 = 2 1 ( b k + 1 ) 2 + 2 1 , for all k the minimum of f ( k ) is 2 1 . (automatically discarding i ) . )
∴ n = 1 ∑ 2 0 1 7 h ( n ) 3 = 2 0 1 7 ⋅ 8 1 = 2 5 2 . 1 2 5 .